2003
DOI: 10.1080/0301446031000091792
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric and body composition indicators of Bahraini adolescents

Abstract: A trend of greater obesity appears to have occurred in the Bahraini adolescents during the period between 1986 and 2000. These findings have important public health implications given recent evidence linking childhood and adolescent obesity to increased risk of obesity and morbidity in adulthood. Therefore, programmes to prevent the development of obesity in children and adolescents should be given a high priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
18
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 17 publications
3
18
4
Order By: Relevance
“…The authors expressed concern over a rising trend for obesity, especially in girls, and emphasized the need for intervention programs 2. The findings of Al-Sendi et al in 2003 further confirmed the increasing weight gain among the adolescent population 1. The current research was conducted on a large and representative sample of Bahraini school children and adlolescents aged 6 to 18 years from all the populated regions of the country and formed one of the components of a comprehensive assessment of nutritional status, particularly, anthropometric status (height, weight, body mass index, subscapular skin fold, triceps skinfold thickness, midarm circumference and arm muscle area).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The authors expressed concern over a rising trend for obesity, especially in girls, and emphasized the need for intervention programs 2. The findings of Al-Sendi et al in 2003 further confirmed the increasing weight gain among the adolescent population 1. The current research was conducted on a large and representative sample of Bahraini school children and adlolescents aged 6 to 18 years from all the populated regions of the country and formed one of the components of a comprehensive assessment of nutritional status, particularly, anthropometric status (height, weight, body mass index, subscapular skin fold, triceps skinfold thickness, midarm circumference and arm muscle area).…”
mentioning
confidence: 91%
“…Growth patterns are indicators of nutritional status of children and are important in developing intervention programs 19. Previous nutritional surveys in Bahrain were limited in their scope and sampling.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are more accurate methods of determining the body fat content such X-ray absorptiometry (DXA), these methods are not practical for epidemiological studies (7) . In turn, indirect measures such as waist circumference (WC), skinfold, arm circumference (AC), waist-to-hip ratio (WHR) and the waist-to-stature ratio (WSR), are methods that can be used to assess adiposity (8) . The present study aimed to examine the occurrence of inadequacy in biochemical levels in obese adolescents and to evaluate their relationship with anthropometric indicators of abdominal or generalised adiposity as a screening instrument for discriminating individuals at high cardiometabolic risk.…”
Section: Introductionmentioning
confidence: 99%
“…In reality these ndings did not try to discuss the growth and development issues as 10,20 . In high performance training, the speci c features (anthropometric) for the di erent sports -height, sitting height and size of limbs -have been given special attention by several scholars 16,[23][24][25] . e maturational aspects, which have also been given attention due to their variations (early or late), are often attributed to the intensive training for elite performance in the di erent sports, particularly in AG 5,8,21,[26][27] .…”
Section: Introductionmentioning
confidence: 99%